Pelatihan Kesadaran Pajak Untuk Berpartisipasi Dalam Pelaksanaan Edukasi Perpajakan Bagi Mahasiswa dan non Mahasiswa Calon Relawan Pajak Kanwil DJP Jateng 2 - Mujiati Mujiati; Kurnia Rina Ariani2; M. Abdul Aris (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2023)
The Tax Volunteer Program rolled out by the government aims to train students and non-students to be ready to assist taxpayers in the Central Java Regional Office 2 area in fulfilling their obligations by providing adequate training, knowledge and understanding of taxation related to tax reporting through filling out the Annual SPT. The involvement of tax volunteers from non-student elements has just been rolled out in the DJP Central Java 2 office starting in 2023 through the Tax Center. The training provided includes the tax reporting process and the completion of the Annual Tax Return (Annual SPT) as a means of preparation to become a tax volunteer which is useful as a vehicle for students and and non-students consisting of lecturers, entrepreneurs and community leaders are interested in participating in service to the taxpayer community. The existence of these tax volunteers will become ambassadors for the taxpayer community to increase public awareness of the importance of paying taxes. In order for tax volunteers to carry out their duties optimally, they must receive training on how to report taxes by filling out the Annual Tax Return